HZ PEYGAMBER (A.S)’İN SAHABE İÇTİHATLARI KARŞISINDAKİ TAVRI - Sahip Beroje (İslami İlimler Dergisi)
İjtihat is a foundation which win Muslim jurisprudence a dynamism. Because of this importance, the Prophet urged Ashab on ijtihat and he appreciated them when they found the truth, and praised even when they did wrong. İn this study it has been examined what we should understand from the Prophet’s attitudes against Ashab’s ijtihats in terms of religious-legal point by giving examples from Sahabe’s ijtihats.